2021
DOI: 10.1161/jaha.121.021198
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine in Patients With Coronary Artery Disease: A Systematic Review and Meta‐Analysis of Randomized Trials

Abstract: Background Inflammation plays a pivotal role in coronary artery disease (CAD). The anti‐inflammatory drug colchicine seems to reduce ischemic events in patients with CAD. So far there is equipoise about its safety and impact on mortality. Methods and Results To evaluate the utility of colchicine in patients with acute and chronic CAD, we performed a systematic review and meta‐analysis. MEDLINE, EMBASE, Cochrane CENTRAL and conference abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…From a mechanistic standpoint, the anti‐inflammatory effects of colchicine are not only mediated by direct interaction with microtubules and by regulation in cytokine secretion but also due to modifications at the transcriptional level 14 . Thus, longer therapy durations (such as > 28 days) are necessary to establish the full effects of colchicine; thus, we enrolled patients who had tolerated colchicine for > 28 days 15 , 16 . In the DM cohort, the colchicine users had higher frequency of pneumonia than nonusers; therefore, we set the 28-day cutoff point to observe tolerance for colchicine 17 .…”
Section: Methodsmentioning
confidence: 99%
“…From a mechanistic standpoint, the anti‐inflammatory effects of colchicine are not only mediated by direct interaction with microtubules and by regulation in cytokine secretion but also due to modifications at the transcriptional level 14 . Thus, longer therapy durations (such as > 28 days) are necessary to establish the full effects of colchicine; thus, we enrolled patients who had tolerated colchicine for > 28 days 15 , 16 . In the DM cohort, the colchicine users had higher frequency of pneumonia than nonusers; therefore, we set the 28-day cutoff point to observe tolerance for colchicine 17 .…”
Section: Methodsmentioning
confidence: 99%
“…Fiolet et al reported the levels of CRP, an inflammatory marker, decreased after 1 month of colchicine treatment, and the MRI findings of myocarditis revealed improvement, thus supporting this finding (39). Similar to meta-analysis of Kofler et al report, the use of colchicine for > 150 days resulted in the lowest risk of HD (40). Thus, colchicine can be used for a long term without drug resistance in HD.…”
Section: Discussionmentioning
confidence: 70%
“…Initial studies demonstrated that allopurinol, a xanthine oxidase inhibitor, was associated with improved endothelial function in HF patients. 17 Subsequently, the Effects of Xanthine Oxidase Inhibition on Hyperuricemic Heart Failure Patients (EXACT‐HF) study randomized patients (with primarily NYHA Class II and III HFrEF and hyperuricemia) to allopurinol (target dose 600 mg daily) versus placebo for 24 weeks. 18 The primary outcome, a composite clinical end point based on several factors including survival, worsening HF, and patient global assessment, was not significantly different between the allopurinol and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, uric acid lowering therapies have been considered potential medication candidates for improving HF outcomes. Initial studies demonstrated that allopurinol, a xanthine oxidase inhibitor, was associated with improved endothelial function in HF patients 17 . Subsequently, the Effects of Xanthine Oxidase Inhibition on Hyperuricemic Heart Failure Patients (EXACT‐HF) study randomized patients (with primarily NYHA Class II and III HFrEF and hyperuricemia) to allopurinol (target dose 600 mg daily) versus placebo for 24 weeks 18 .…”
Section: Discussionmentioning
confidence: 99%